The road to Dalton - Bowring, Shannon (New York : Europa Editions, 2023)
It's 1990. In Dalton, Maine, life goes on. Dr. Richard Haskell tends to the health of his community while his wife, Trudy, carries on an affair with her best friend $1 (Ba fact both accepted and ignored by their husbands. Rookie cop Nate Theroux strives to do his best for his hometown, while his wife silently suffers from postpartum depression. Rose struggles within an abusive relationship, and fourteen-year-old Greg tries to define the complicated feelings he has for his two friends. And when one local makes an unthinkable decision that leaves Dalton reeling, its residents are forced to confront the truth that no one is exactly who we think they are.s
Includes reading guide.
Maine author.
Keywords: Small towns -- Fiction; Postpartum depression -- Fiction; Family secrets -- Fiction; Lesbians -- Fiction; Homosexuality -- Fiction; Gay teenagers -- Fiction; Mental health -- Fiction; Maine -- Fiction; Historical fiction; Domestic fiction